Mechanical, tribological and corrosion physiognomies of CNT-Al metal matrix composite (MMC) coatings deposited by cold gas dynamic spray (CGDS) process - Zhang, Yingpeng; Wang, Qun; Chen, Gang; Ramachandran, Chidambaram Seshadri (Surface & coatings technology, 2020)
A 1 wt% carbon nanotube‑aluminum (CNT-Al) metal matrix composite (MMC) powder was prepared using a polymer pyrolysis chemical vapor deposition (PP-CVD) coupled high energy ball milling (HEBM) method and the resultant MMC powder was spray deposited as a protective coating on the surface of AZ91 Mg alloy by the cold gas dynamic spray (CGDS) process. The coating microstructure, phase composition, mechanical properties, corrosion, and dry sliding wear (tribological) resistances were compared to the properties of CGDS pure Al coating. The results show that the coatings prepared by CGDS has not undergone any stoichiometric change and CNT as well as Al4C3 phases that were originally present in the CNT-Al feed-stock powder were well preserved in the resultant MMC coatings. In addition, the number and size of the pores in the CNT-Al MMC coating are significantly lower than that of the pure Al coating. The average hardness and elastic modulus of the CNT-Al MMC coating were 1.66 GPa and 77.6 GPa, which were 112.8% and 11.7% higher than those of the pure Al coating, respectively. The corrosion current density and wear rate of the CNT-Al MMC coating were 2.030 × 10−6 A/cm2 and 9.34 × 10−4 mm3/N·m respectively, which were one order of magnitude lower compared to the pure Al coating, highlighting the excellent corrosion and wear resistance of CNT-Al MMC coating. •CNT-Al coating was prepared by PP-CVD coupled HEBM method combined with CS process.•CNTs-Al coating with high hardness and modulus•CNT-Al coating has excellent corrosion resistance and wear resistance.•The CNT will form a graphite layer during the wear process to reduce the wear rate.